1999
DOI: 10.1207/s15327914nc352_4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Treatment of Colon Adenocarcinoma With Crocin, a Carotenoid From Saffron (Crocus sativus L.): An Experimental Study in the Rat

Abstract: We used an experimental model in the rat to examine the effects of long-term treatment with crocin, a glycosylated carotenoid from the stigmas of the saffron crocus, on colon cancer. BD-IX rats were divided into four groups: Groups G1 and G2, designated "cancer groups," were used to study the effects of crocin on the progression of colon cancer, and Groups G3 and G4, designated "toxicity groups," were used to study the effects of the treatment on metabolic processes and the parenchyma. DHD/K12-PROb cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 8 publications
6
63
0
4
Order By: Relevance
“…Abdullaev and Frenkel also showed that saffron could exert inhibitory effect on cellular DNA and RNA synthesis, but not on protein synthesis Frenkel, 1992a, 1992b). Cancer chemopreventive as well as antitumor activities were also reported for crocins and crocetin derivatives in different assay systems (Tarantilis et al, 1994;Wang et al, 1995;Escribano et al, 1996;Konoshima et al, 1998;Garcia-Olmo et al, 1999;Aung et al, 2007).…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 91%
“…Abdullaev and Frenkel also showed that saffron could exert inhibitory effect on cellular DNA and RNA synthesis, but not on protein synthesis Frenkel, 1992a, 1992b). Cancer chemopreventive as well as antitumor activities were also reported for crocins and crocetin derivatives in different assay systems (Tarantilis et al, 1994;Wang et al, 1995;Escribano et al, 1996;Konoshima et al, 1998;Garcia-Olmo et al, 1999;Aung et al, 2007).…”
Section: Effect Of Saffron and Crocin On Mms-induced Dna Damagementioning
confidence: 91%
“…Saffron, and some of its bioactive components, have also been shown to possess antitumor activity, but as observed in the research with cumin seeds, varied responses to saffron and its bioactive components have been observed in different types of cultured malignant cells (97). There also been a differential response noted between male and female rats with colon adenocarcinomas to crocin (a compound in saffron) which indicates the potential involvement of hormonal factors in tumorigenesis (98).…”
Section: Inflammation-sincementioning
confidence: 99%
“…[1,3,[7][8][9][10][11][12][13][14] In parallel, the possible uses of saffron and its active constituents lead to an increasing number of research studies, some of which have drawn some very useful and intriguing results of active ingredients of saffron, especially against malignancies, cardiovascular and Alzheimer's disease. [15][16][17][18][19][20][21][22] In this minireview, we aim to summarize and critically address previous and current evidence regarding the biological/ pharmacological activities of saffron and its active ingredients and their possible therapeutic uses. The history and structural features of saffron constituents are given in the first part of the review, followed by a comprehensive and critical presentation of the published preclinical and clinical studies and review papers on the pharmacology and potential therapeutic applications of saffron and its main active components.…”
Section: Introductionmentioning
confidence: 99%